Structural change in liquid sulphur from chain polymeric liquid to atomic simple liquid under high pressure. (21st March 2019) - Ohmura, S; Shimojo, F
Abstract: The structural properties of liquid sulphur under high pressure up to approximately 500 GPa have been investigated by means of ab initio molecular-dynamics (MD) simulations. The obtained pair distribution functions and spatial distribution of electron density under high pressure indicate the existence of a covalent-like interaction even in the metallic state and the covalent-like interaction gradually decreases with increasing pressure. By analyzing the static structure factor, it is found that the covalent-like interaction still remains at approximately 200 GPa, and liquid sulphur has a simple liquid structure at 320 GPa and higher pressures. These results indicate that the covalent-like interaction disappears at a pressure between 200 and 320 GPa. In this study, we also estimate the pressure range of structural change in other liquid chalcogens in a similar manner as liquid S. The pressures at which liquid Se and Te have simple liquid structure are estimated to be larger than approximately 100 and 20 GPa, respectively.